Brain Metastases and Place of Antiangiogenic Therapies in Alveolar Soft Part Sarcoma: A Retrospective Analysis of the French Sarcoma Group. (9th January 2019) - Malouf, Gabriel G.; Beinse, Guillaume; Adam, Julien; Mir, Olivier; Chamseddine, Ali N.; Terrier, Philippe; Honore, Charles; Spano, Jean‐Philippe; Italiano, Antoine; Kurtz, Jean‐Emmanuel; Coindre, Jean‐Michel; Blay, Jean‐Yves; et al.
Abstract: Background: Alveolar soft part sarcoma (ASPS) is a rare sarcoma characterized by a slow evolution, brain metastasis (BM), and resistance to doxorubicin. Antiangiogenic therapies (AAT) have shown clinical activity, but little is known about the optimal therapeutic strategy, specifically considering BM. Subjects, Materials, and Methods: We performed a retrospective analysis of all patients with ASPS treated in three referral centers of the French Sarcoma Group. We aimed to describe factors associated with overall survival (OS) and the impact of BM on outcome of patients treated by AAT. Results: We identified 75 patients between 1971 and 2012 (median age = 23, range: 5–96 years). Median follow‐up was 74 months. Patients with localized ( n = 44, 59%) and metastatic ( n = 31, 41%) diseases had a 10‐year OS of 69% and 25%, respectively. Only surgical incomplete resection was associated with shorter OS in localized disease (hazard ratio [HR] = 5.2, 95% confidence interval [CI] 1.2–22.4, p = .02). Fifty‐two (69%) patients developed lung metastasis (LM; baseline: n = 31, [41%]; de novo: n = 21, [28%]). Thirteen patients developed BM, all occurring after LM. Tumor size ≥5 cm was associated with poorer BM‐free survival (HR = 8.4, 95% CI 2.1–33.9, p = .002). Median OS post‐BM was 17 months (95% CI 15 to not assessable). Overall, 12 patients were treated with AAT (sunitinib n = 10): 5 patients had BM and achieved poor outcomes compared with patients without, with median progression‐free‐survivals of 2 versus 11 months, respectively. Conclusion: Baseline larger tumors were associated with increased risk of brain metastasis in patients with ASPS. Patients with BM seem to have little benefit from AAT, suggesting the need to develop antineoplastic agents with high central nervous system penetrance in this setting. Abstract : The effect of anti‐angiogenic therapies in alveolar soft part sarcoma patients with metastatic disease remains to be clarified. This article analyzes clinical factors associated with patient outcomes with a focus on the natural history of brain metastasis and patient response to anti‐angiogenic therapies.